The efficiency of heart protection with HTK or HTK-N depending on the type of ischemia - Schäfer, Michael; Gebhard, Martha-Maria; Gross, Wolfgang (Bioelectrochemistry, 2019)
We investigated isolated guinea pig hearts (n=121) in an ischemia/ reperfusion model with the aim to compare the efficiency of the cardioplegic solution HTK with its novel replacement HTKN. Following consolidation with Tyrode's solution, ischemia started either immediately or after preceding cardioplegia with HTK, HTKN, or modified HTK enriched with Ca. Ischemia lasted either 80min at 30°C, or 360min at 5°C, or 81min at 30°C with intermittent cardioplegic perfusion. During ischemia we measured intracellular calcium (iCa++) and the time of gap junction uncoupling (t-in). During reperfusion we measured the reestablishment of cell coupling (t-ret), left ventricular developed pressure (LVDP), and heart rhythm (VC-RR). In 5°C groups, iCa++ at t-in was significantly higher than before ischemia, and longest t-in, shortest t-ret, and best VC-RR were observed after HTK-protection. Of all 30°C groups, the intermittent group with modified HTK showed shortest t-ret, best VC-RR, and the highest LVDP. At 5°C, HTK groups had higher LVDP than HTK-N groups, but not at 30°C. The data suggest that the higher calcium level in the HTK-N solution improves reperfusion after short ischemia at 30°C but for long lasting ischemia at 5°C it is beneficial to use the HTK solution.